(untitled) (Research, Society and Development, 2022)
A Plackett-Burman factorial design with 15 experiments was conducted to evaluate the influence of seven factors on lipases production by Fusarium solani. The factors investigated were peptone, tryptone, yeast extract, calcium chloride, potassium phosphate, magnesium sulfate, and copper sulphate. Five fixed variables (cotton oil, pH, temperature, agitation, and time) were maintained and as a response to the enzymatic activity. The concentration of tryptone, calcium chloride, and magnesium sulphate had a significant effect (p < 0.10) on lipase production and was studied consecutively through a complete DCCR (central rotational compound design), to optimize lipase production of the fungi F. solani. After optimization using DCCR, maximum lipolytic activities of 24.84 U/ml were obtained with the use of 10 g.L-1 tryptone, 3.50 g.L-1 calcium chloride and 0.50 g.L-1 magnesium sulfate, 1 g.L-1 potassium phosphate and 1% soybean oil. The statistical model showed a correlation of 85.67% with the experimental data. The biochemical characterization of lipase showed that the enzyme has a better performance at pH 7 at a temperature of 40 °C, where the statistical model had a correlation of 94.15% with the experimental data. In this way, lipases produced by F. solani have potential for application and use in biodiesel production.